2018
DOI: 10.1152/ajpcell.00342.2016
|View full text |Cite
|
Sign up to set email alerts
|

P2Y receptor regulation of K2P channels that facilitate K+ secretion by human mammary epithelial cells

Abstract: The objective of this study was to determine the molecular identity of ion channels involved in K secretion by the mammary epithelium and to examine their regulation by purinoceptor agonists. Apical membrane voltage-clamp experiments were performed on human mammary epithelial cells where the basolateral membrane was exposed to the pore-forming antibiotic amphotericin B dissolved in a solution with intracellular-like ionic composition. Addition of the Na channel inhibitor benzamil reduced the basal current, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…To reflect the heterozygous probands, we coexpressed equal amounts of WT and mutant TASK-1 mRNAs and measured their inhibition by either carbachol via endogenous muscarinic receptors or ATP via a coexpressed P2Y receptor 44 , 45 . We found that GPCR-mediated inhibition by either approach was markedly impaired in all DDSA mutant homomeric channels (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To reflect the heterozygous probands, we coexpressed equal amounts of WT and mutant TASK-1 mRNAs and measured their inhibition by either carbachol via endogenous muscarinic receptors or ATP via a coexpressed P2Y receptor 44 , 45 . We found that GPCR-mediated inhibition by either approach was markedly impaired in all DDSA mutant homomeric channels (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To reflect the heterozygous probands, we co-expressed equal amounts of WT and mutant TASK-1 mRNAs and measured their inhibition by either carbachol via endogenous muscarinic receptors, or by ATP via a coexpressed P2Y receptor as reported previously 41,42 . However, unlike WT TASK-1, we found that GPCR-mediated inhibition by either approach was markedly impaired in all 'heterozygous' DDSA mutant co-expressions (Fig.…”
Section: Ddsa Mutations Results In Defective X-gating and Dysfunctional Gpcr-mediated Inhibition Task Channels Have Been Shown Be Inhibitmentioning
confidence: 99%
“…To validate the detrimental effects caused by genetic knockout in Kcnk9 -/mice, we specifically blocked KCNK9 using the recently described substance [4,3-d]pyrimidin-4-yl]-4-piperidinyl]-1-butanone (PK-THPP) in wildtype and knockout animals and again acutely induced colitis with DSS treatment. 14,15 Pharmacologic inhibition of KCNK9 severely affected wild-type animals as indicated by weight loss (Figure 2A) and disease activity index (Figure 2B), but did not further modify the disease course of knockout animals. Barrier disruption also was more substantial in PK-THPP-treated wild-type animals (Figure 2E).…”
Section: The Phenotype Of Kcnk9-deficient Mice Can Be Reproduced By P...mentioning
confidence: 99%
“…On days 6-9, mice received normal drinking water. One experimental group received PK-THPP, a potent antagonist of KCNK9, 14,15 which was administered intraperitoneally once daily throughout the experiment (10 mg/g body weight in 200 mL 1% dimethyl sulfoxide [DMSO]/40% polyethylene glycol 400/phosphatebuffered saline [PBS]) (DMSO; polyethylene glycol 400) Q22 , Sigma Aldrich, St. Louis, MO). Control animals received 200 mL 1% DMSO/40% polyethylene glycol 400/PBS intraperitoneally.…”
Section: Experimental Model Of Colitis and Barrier Permeability Assaymentioning
confidence: 99%